The Black Madonna: A Theoretical Framework for the African Origins of Other World Religious Beliefs - Michello, Janet (Religions, 2020)
This review summarizes existing scholarship in order to theorize how Abrahamic religions and Hinduism were influenced by African beliefs, in order to illuminate the contributions that African beliefs have had on other world religions. The review begins with a brief historical overview of the origins of indigenous ideologies, followed by a review of classical theories of religion and a summary of contemporary religious trends, with particular attention on African beliefs. The Black Madonna, with origins in Africa, is a prominent example of how African beliefs have been integrated into other faiths in ways that are often obscured from view. The Black Madonna is compared with the characteristics and symbolism of the traditional fair-skinned Virgin Mary. It is estimated that there are hundreds of depictions of the Black Madonna, yet her identity as truly black is generally minimized. This review contributes a theoretical rationale for the lack of recognition and acceptance of the Madonna as black, contextualizing this within a feminist theoretical viewpoint and analyzing the connection to African folklore and traditional religious beliefs. The theoretical framework articulated in this paper contributes an elucidation of the ways that indigenous African religions have affected other world religions. Acknowledging this influence challenges the simplistic notion of reified distinctions between Western and non-Western religions.